The Correlation Between Posture, Duration of Gadget Usage and Physical Activity during COVID-19 Pandemic to The Occurrence of Neck Pain among Medical Students in Udayana University - Soetomo, Cindy Thiovany; Primayanti, I Dewa Ayu Inten Dwi; Sundari, Luh Putu Ratna (Sport and Fitness Journal, 2022)
ABSTRACT Increased duration of gadget usage since COVID-19 pandemics can cause various negative impacts if implemented without considering ergonomic factors, especially body and neck posture. One of those impacts that often found is musculoskeletal disorders like neck pain due to excessive cervical flexion load. However, incidence of neck pain also affected by many other factors, such as physical activity and exercise habit. This study aims to determine the correlation between posture, duration of gadget usage, and physical activity during COVID-19 pandemic to the occurrence of neck pain among Medical Students in Udayana University. An analytical observational study was conducted with cross-sectional approach using questionnaire adapted from Nordic Musculoskeletal Questionnaire to measure quantity and quality of neck pain of 106 medical students in Udayana University. The correlation between variables was then analyzed by Chi-square test. Results of this study showed that 77.4% of medical students in Udayana University usually use gadget ?56 hours a week and 61.3% of medical students have experienced neck pain in last 12 months during COVID-19 pandemic. Analytical study showed that correlation between posture and neck pain has p-value = 0.016 (<0.05), physical activity and neck pain has p-value = 0.012 (<0.05), while duration of gadget usage and neck pain has p-value = 0.733 (>0.05). It can be concluded that there are significant correlations between posture while using gadget and physical activity to neck pain, but there is no significant correlation between duration of gadget usage and neck pain during COVID-19 pandemic among medical students in Udayana University. Keywords : posture; duration; gadget; physical activity; neck pain; medical students